Analysis of CVT (continuously variable transmission) and the influence of variations on the motorcycle - Rinasa Agistya Anugrah (Jurnal Penelitian Saintek, 2022)
This study was aimed to determine the working principle, troubleshooting, and the influence of CVT roller weight variations on Suzuki Nex-FI 2014 motorcycles. This research was conducted by analyzing and comparing the measurement results for each CVT component. This study used an experimental research by holding the throttle at 3,250 rpm. Once steady state is reached, the throttle is rotated up to 10,000 rpm. The results of the troubleshooting analysis and measurement of drive belt wear were from the standard size of 19.50 mm to 18.00 mm. The usage tolerance limit is 18.60 mm. As for the results of the roller variation test using a lighter weight namely 8 and 9 grams. The results show that the maximum results are achieved at low and medium rotational speeds, compared to the use of 11 gr (standard) roller. The weakness of the lighter roller (8 9 grams) is that they only get good acceleration and torque at low revs while at high rotation speed is less than the maximum. The use of standard (11 gram) roller has less maximum acceleration and torque but produces maximum power.